Advances in materials manufacturing science and technology XIV selected, peer reviewed papers from the 14th International Manufacturing Conference in China (IMCC2011), October 13-15, 2011, Tianjin, China - Huang, Tian (Materials science forum, 2011)
This book contains selected papers from the 14th International Manufacturing Conference, IMCC2011, held in China. The papers disclose the latest developments in the field of materials manufacturing technology: from fundamentals to new technologies and applications. In particular, these papers cover the topics of advanced manufacturing technology and equipment, materials-forming science and technology, digital manufacturing systems and management, modern design theory and methodology, and MEMS and Ultra-precision machining. Review from Book News Inc.: An October 2011 conference offered a forum to discuss innovative research, recent technology, and emerging application trends in the fields of advanced manufacturing technology, modern management, and design theory and methodology. This book offers a total of 172 peer-reviewed papers from the conference, written by researchers and industrial practitioners. Material is organized into sections on advanced manufacturing technology and equipment, material-forming science and technology, digital manufacturing systems and management, modern design theory and methods, and MEM and ultraprecision manufacturing. Some specific topics include laser shock processing of Ni-base supperalloy and high-cycle fatigue properties, the effect of square wave AC parameters on weld forming performance, the dissolution mechanism of copper weld brazing with Cu-based brazing alloys, and a morphological filtering algorithm for estimation of tool wear in CNC milling machining. Other subjects investigated are buckling optimization of perforated curved shells, stability analysis of a processor unit in a deep-sea application, error modeling for a master slave surgical robot system, and advanced optics applications using ultra-precision free-form machining technology. B & w photos are included.